The importance of sports and physical education in the development of collective skills in a multicultural student community - Mironova O.V. ,; Yarchikovskaya L.V. ,; Sharonova A.V. ,; Vashchuk O.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study. This study aims to prove the importance of physical activity in the development of collectivist qualities in a multicultural student environment. Methods and structure of the study. 256 students of St. Petersburg State University (St. Petersburg State University) participated in the experiment, of which 48 were involved in a pedagogical experiment. The participants were conditionally divided into two groups based on the specifics of their relationships and the level of development of collectivism: the control (CG, n=23) and the experimental (EG, n=25) groups. The research methodology included pedagogical observations and experimental work, questionnaires, and analysis of independent assessments. Results and conclusions. The article presents the experience of developing a sense of collectivism in a multinational student environment. It has been experimentally shown that the use of team-building games and tasks in physical education and sports classes has a positive effect on the establishment of interpersonal relationships in the student body and the formation of collective values among students. Therefore, the analysis of the research results confirms the hypothesis about the influence of physical culture on the formation of a team in a multinational student environment.